The Study of Alginate and Whey Protein Hydrolyzed Suplementation Utilization for Cell Release and Microencapsulated Lactobacillus Acidophilus Viability in Probiotic Ice Cream - Purwadi Purwadi; Abdul Manab; Khoiruman Khoiruman (Faculty of Animal Science Universitas Brawijaya, 2011)
The objectives of this research were to increase viability and activity of L. acidophilus encapsulated with alginate and whey protein hydrolyzed for cell release and microencapsulated Lactobacillus acidophilus viability in probiotic ice cream. The methods used were factorial experiment using Completely Randomized Design. Data was analysed with Variance Analysis. The results showed that the interaction between alginate and whey protein hydrolyzed supplemented could be increased the function of CaCl2 and also encapsulated L. acidophilus viability. The used alginate of 1% and whey protein hydrolyzed supplemented of 0,5% produced encapsulated L. acidophilus viability higher than before, but however, the utilization of alginate of 1% and whey protein hydrolyzed supplemented of 0% could release a few cell. Therefore, the utilization of alginate 1% and whey protein hydrolyzed supplemented 0,5% in ice cream produced L. acidophilus highest than other. Â Keywords :Â Â Lactobacillus acidophilus, microencapsulation, alginate, whey protein hydrolyzed, cell release, ice cream